Compact carbon dioxide sensor using tunable diode laser absorption spectroscopy for capnographic monitoring. Issue 3 (16th March 2022) - Li, Jinyi; Cheng, Xinyu; Tian, Xinli; Zhao, Hang; Li, Lianhui
Abstract: In order to realize real-time capnographic monitoring, a compact carbon dioxide sensor based on tunable diode laser spectroscopy technology was developed by means of a 2004 nm distributed feedback laser and a circular gas cell. The toroidal cell can achieve an optical path length of 3.49 m in a volume of 38 ml, which enables the tunable diode laser spectroscopy carbon dioxide sensor to achieve a detection limit of 175 ppm at a measurement rate of 12.5 Hz. The actual exhaled carbon dioxide gas detection experiments were implemented, including the breath analysis of a normal subject under different conditions and another subject with pneumothorax. It indicates that the sensor has good effectiveness and practicability for carbon dioxide metabolic monitoring and related disease diagnosis.